Family’s Health-Strategy in Brazil: An Analysis of its Applicability - Luiz Antonucci; Maria das Dores de Loreto; Amelia Bifano; Edna Miranda; Diego Procópio (Íconos)
This article studies the Brazilian public health policy – Family’s Health Strategy (ESF by its Spanish acronym) - verifying, through the analysis of daily life, its organization, functioning and social networks around it. The research was carried out in a Primary Health Care Unit (UAPS by its Spanish acronym), where a documentary analysis of the ESF criteria was held through direct non-participatory observation, self-confrontation interviews and the study of social networks mobilized by professionals and users of this Unity. The results show, on the one hand, that in spite of the application of the principles and guidelines of the ESF in the procedures required by the UAPS, in practice, the profile that their professionals have built is the essential tool to assure the final quality of the work. And, on the other hand, the role of social networks around health reveals the strength of informal relationships and the fragility of the link between the State and the citizens.